The Implementation of Blended Learning in Teaching English at Senior High School in Sidoarjo - Firdaus, Anita; Astutik, Yuli (New Language Dimensions, 2021)
Blended learning is a learning strategy that combines face-to-face learning (both traditional in-class and virtually with video conferences) with online learning (e-learning). Blended learning is used as the best solution for dealing with restrictions on large-scale activities in Indonesia due to the spread of the coronavirus. SMAN 1 Porong applies blended learning to ensure the teaching and learning process continues, especially in learning English. On the other hand, teachers in this school face challenges in implementing blended learning. Therefore, the purposes of this study are to reveal in detail the implementation of blended learning and the challenges faced by teachers using case study research. To collect data, the researchers used observation and unstructured interview techniques. The results of this study indicate that SMAN 1 Porong has successfully implemented blended learning, especially for English lessons. However, the English teachers at the school are not free from challenges, such as the difficulty of finding the right strategy for face-to-face and online classes. This study implies that, however, the success of blended learning must be accompanied by teachers' creativity in teaching both face-to-face and online and the support of school facilities.